The method of quantitative sensory testing in the diagnostics of facial chronic pain syndromes - M. N. Sharov; D. I. Nakhrapov (Лечащий Врач)
Quantitative sensory testing is one of the objective method in assessing and diagnosing chronic facial pain syndromes. 155 patients with trigeminal neuralgia, trigeminal neuropathy, myofascial pain syndrome with temporomandibular disorder were examined. Conclusions were drawn about the sensory patterns of various chronic pain syndromes in the facial area. A new term was proposed «differentiated sensory alteration» is the differentiated interest of C- and A-delta-fibers, which are responsible for assessing the organism’s thermal and cold sensitivity, in the development of chronic pain syndromes.